Natural fiber-reinforced polycaprolactone green and hybrid biocomposites for various advanced applications - R. A., Ilyas; M. Y., M. Zuhri; Norrrahim, Mohd Nor Faiz; Mohamad Misenan, Muhammad Syukri; Jenol, Mohd Azwan; Samsudin, Sani Amril; Nurazzi, N. M.; Asyraf, M. R. M.; Supian, A. B. M.; Bangar, Sneh Punia; Nadlene, R.; Sharma, Shubham; et al. (MDPI, 2021)
Recent developments within the topic of biomaterials has taken hold of researchers due to the mounting concern of current environmental pollution as well as scarcity resources. Amongst all compatible biomaterials, polycaprolactone (PCL) is deemed to be a great potential biomaterial, especially to the tissue engineering sector, due to its advantages, including its biocompatibility and low bioactivity exhibition. The commercialization of PCL is deemed as infant technology despite of all its advantages. This contributed to the disadvantages of PCL, including expensive, toxic, and complex. Therefore, the shift towards the utilization of PCL as an alternative biomaterial in the development of biocomposites has been exponentially increased in recent years. PCL-based biocomposites are unique and versatile technology equipped with several importance features. In addition, the understanding on the properties of PCL and its blend is vital as it is influenced by the application of biocomposites. The superior characteristics of PCL-based green and hybrid biocomposites has expanded their applications, such as in the biomedical field, as well as in tissue engineering and medical implants. Thus, this review is aimed to critically discuss the characteristics of PCL-based biocomposites, which cover each mechanical and thermal properties and their importance towards several applications. The emergence of nanomaterials as reinforcement agent in PCL-based biocomposites was also a tackled issue within this review. On the whole, recent developments of PCL as a potential biomaterial in recent applications is reviewed.